Use of liraglutide and risk of major cardiovascular events: a register-based cohort study in Denmark and Sweden. Issue 2 (February 2019) - Svanström, Henrik; Ueda, Peter; Melbye, Mads; Eliasson, Björn; Svensson, Ann-Marie; Franzén, Stefan; Gudbjörnsdottir, Soffia; Hveem, Kristian; Jonasson, Christian; Pasternak, Björn
Summary: Background: Trial evidence shows that the glucagon-like peptide-1 receptor agonist liraglutide significantly reduces the risk of major cardiovascular events among patients with type 2 diabetes who have established cardiovascular disease or are at high cardiovascular risk. We aimed to assess the cardiovascular effectiveness of liraglutide in routine clinical practice. Methods: We used data from nationwide registers in Denmark and Sweden for the period from Jan 1, 2010, to Dec 31, 2016, to investigate the risk of major cardiovascular events associated with use of liraglutide, compared with an active comparator drug class, dipeptidyl peptidase-4 (DPP-4) inhibitors, in patients with type 2 diabetes. The cohort included incident users of liraglutide or DPP-4 inhibitors, who were also using metformin at baseline, matched 1:1 on age, sex, and propensity score. The main outcome was major cardiovascular events, a composite outcome consisting of myocardial infarction, stroke, and cardiovascular death. Other outcomes assessed were the individual components of the main composite outcome, heart failure, death from any cause, and an expanded composite major cardiovascular events outcome that also included other ischaemic heart disease, coronary revascularisation, and peripheral arterial disease. Findings: The study population consisted of 23 402 users of liraglutide and 23 402 matched users of DPP-4 inhibitors; patients were followed up for a mean of 3·3 years (SD 2·0). A major cardiovascular event occurred in 1132 users of liraglutide (incidence rate 14·0 per 1000 person-years) and in 1141 users of DPP-4 inhibitors (15·4 per 1000 person-years; hazard ratio [HR] 0·90, 95% CI 0·83–0·98). The HRs were 0·81 (0·71–0·92) for patients with a history of major cardiovascular disease and 0·96 (0·86–1·06) for patients without such a history (p=0·057 [test of homogeneity], suggesting no statistical evidence of heterogeneity). Compared with use of DPP-4 inhibitors, use of liraglutide was associated with a significantly lower risk of cardiovascular death (HR 0·78, 95% CI 0·68–0·91), but no significant differences were identified for risk of myocardial infarction (0·94, 0·84–1·06) or stroke (0·88, 0·77–1·01). Furthermore, use of liraglutide was associated with a significantly lower risk of death from any cause (HR 0·83, 95% CI 0·77–0·90), but no significant differences were identified for risk of heart failure (0·90, 0·80–1·03) or for the expanded major cardiovascular events outcome (0·95, 0·89–1·01). Interpretation: In this large Scandinavian cohort, use of liraglutide, as compared with use of DPP-4 inhibitors, was associated with significantly reduced risk of major cardiovascular events. Patients with history of cardiovascular disease seemed to derive the largest benefit from treatment with liraglutide. These data provide support for the cardiovascular effectiveness of liraglutide in routine clinical practice. Funding: Swedish Heart-Lung Foundation, Novo Nordisk Foundation, and Swedish Society for Medical Research.